Feasibility Study of the Mechanical Cooler System for LiteBIRD - Shinozaki, Keisuke; Odagiri, Kimihide; Yoshihara, Keisuke; Sekimoto, Yutaro; Dotani, Tadayasu; Fujimoto, Ryuichi; Narasaki, Katsuhiro; Yoshida, Seiji; Tsunematsu, Shoji; Isshiki, Masahito; Kanao, Kenichi (Cryogenics (Guildford), 2025)
LiteBIRD is the second strategic large-class mission of JAXA aiming to test inflation models. In this mission, cryogenic telescopes and low-temperature scientific instruments are needed to provide high-sensitivity. A mechanical cooler system will cool these telescopes to 5 K or lower, using the 4K-class Joule Thomson cooler (4K-JT) that provides 4.5 K and the 2K Joule Thomson cooler (2K-JT) that provides 1.7 K, which serve as the precoolers of the multistage adiabatic demagnetization refrigerator (ADR). The 20K-class double-stage Stirling coolers (2ST) are also used as precoolers for the JT coolers and shield coolers. This paper presents a feasibility study of the mechanical cooler system and the status of these cooler developments. •A cryogen-free mechanical cooler system is proposed for the LiteBIRD payload module.•The 4K-JT provides 4.5 K and the 2K-JT provides 1.7 K.•The heat exchanger length is proposed based on the cooling performance test.•The heater control is needed at the 2K-JT cold tip and the 1.75 K stage to satisfy a required temperature stability.•The 2ST compressor was upgraded to prevent a mechanical wear and reduce a vibration levels.